Neck dissection versus "watchful-waiting" in early squamous cell carcinoma of the tongue our experience on 127 cases. (December 2016) - Orabona, Giovanni Dell'Aversana; Bonavolontà, Paola; Maglitto, Fabio; Friscia, Marco; Iaconetta, Giorgio; Califano, Luigi
Abstract: Background: Early oral squamous cell carcinoma (EOSCC) represents about 90% of the oral cancers especially in older males. The etiology is multifactorial, strongly related to tobacco and alcohol abuse, but also infective agents, Human papillomaviruses (HPV16-18), genetic factors and pre-neoplastic lesions seem to be implicated. There is no consensus in the literature for the treatment of early squamous cell carcinoma of the tongue (stages I–II); both an elective neck dissection policy and a watchful-waiting policy have their proponents in the different centers. Methods: The records of 127 patients with EOSCC of the tongue treated in our Department between 2007 and 2011, with cN0 neck staging, who underwent resection of the primary tumor with or without elective neck dissection, were reviewed. Results: We divided the patients into two groups, in Group 1 the 66 patients who received an elective neck dissection 30 days later from the primary surgery have been included, and in Group 2 the 61 patients undergoing "watchful waiting" observation for the development of nodal metastases have been collected. Statistical calculations were performed using Chi-square and t student test. Conclusions: A significant difference was found between the two groups as concerns tumor stage and pathologic tumor classification (p < 0.001). No significant differences were present between the two groups as concerns mean follow up (P = 0.2), relapse rate (p = 0.3) and relapse-free survival time (p = 0.2). In T1 stage tumors with depth of infiltration ≤4 mm, or low grade (G1-G2), the "watchful waiting" strategy for cervical metastases is appropriate, given the low regional recurrence rate (15%) and overall survival of 100%. In case of T2 lesions with depth of infiltration ≥4 mm or high grade (G3) we prefer to perform the elective neck dissection, with 13% of local recurrence and 100% of survival at 6 years. Highlights: Data of 127 patients with early oral squamous cell carcinoma were reviewed. In Group 1 were collected 66 patients who received an elective neck dissection. In Group 2 the 61 patients underwent "watchful waiting" observation. Significant difference was found as concerns tumor stage and pTNM. No differences as concerns relapse rate and relapse-free survival time.